Electronic Band Structure of MXene Material (V2C) - Subedi, Dipak Kumar; Shrestha, Rajesh; Shrestha, Sudarshan; Bhattarai, Mohan Raj; Aryal, Bipin (Patan Pragya, 2022)
MXene materials have received a strong boost of interest due to the prediction of behaving as topological dielectric or non conductor which is used in spintronic devices and for future technology device. In this experiment DFT (Density Functional Theory) based Quantum Express code is used to calculate the band structure and DOS of MXene material (i.e. V2C) by setting non-polarized spin polarization framework. From the geometric optimization, lattice parameter is found to be a = 2.945 Å, b = 8.836 Å, c = 28.19 Å. Since its bulk is insulating in nature, we observed MXene layer as conducting i.e. bands overlapping within fermi surface. Similar kind of scenario is observed in DOS which resembles escorted by the previously predicted results.